An improved time domain coupled model of Cross-Flow and In-Line Vortex-Induced Vibration for flexible risers. (15th May 2017) - Yuan, Yuchao; Xue, Hongxiang; Tang, Wenyong
Abstract: Vortex-induced vibration (VIV) is a complicated fluid-structure interaction problem. In this paper, an improved time domain coupled model to predict Cross-Flow (CF) and In-Line (IL) VIV of flexible risers is proposed, which can take the effect of added mass coefficient into account. The functions of non-dimensional amplitude and frequency based on the forced vibration experimental data are developed to obtain VIV hydrodynamic forces. The inertia force terms caused by added mass are simplified as functions of non-dimensional frequency. For CF VIV, the non-dimensional frequency with a range of [0.125, 0.20] is deemed to be the excitation region, while the lock-in and allocation criterion of IL VIV includes 2St and 3St two excitation regions. Coupling effect of CF and IL VIV is taken into consideration by integrating a magnification model for the IL excitation force associated with CF response amplitude. The excitation forces, added mass forces and damping forces are time-varied and would be updated in each step. To verify the developed model, two test models of flexible risers under uniform current are simulated. The envelopes of RMS displacement, time histories of strain, response frequency spectra and added mass coefficients show good agreement with the measured data. Highlights: An improved time-domain prediction model of CF and IL VIV for risers considering the effect of added mass is proposed. The variation effect of added mass influences modal analysis and VIV hydrodynamic force calculation. New lock-in and allocation criterion of 2St and 3St excitation regions in IL direction is established. This improved model is validated, and results are more consistent with experimental data than that of previous model. When stiffness is large or excited modal order is high, the added mass effect on response prediction is quite evident.